2017
DOI: 10.1590/1089-6891v18e-28085
|View full text |Cite
|
Sign up to set email alerts
|

Crude Protein in Diets of European Quails

Abstract: The aim of this study was to evaluate crude protein (CP) levels for European quails from one to 14, 14 to 28 and 28 to 42 days old. The experiment was carried out in a completely randomized experimental design, with five treatments and five replications. No significant effects of CP levels on weight gain and feed conversion from 1 to 14 days were observed, however quails fed 26% CP diets had lower feed intake. The CP levels from 14 to 28 days had significant effect on feed intake, weight gain and feed conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
1
0
2
Order By: Relevance
“…Similar to the result of this study, Murakami et al (1993) had earlier observed a nonsignificant effect of dietary protein level on feed intake of Japanese quails. This is similar to the report of Costa et al (2004) that feed intake is not necessarily controlled by protein levels in the diet, although (Dumont et al, 2017) reported an increase in feed intake among birds fed low crude protein level.…”
Section: Experimental Design and Statistical Analysissupporting
confidence: 89%
“…Similar to the result of this study, Murakami et al (1993) had earlier observed a nonsignificant effect of dietary protein level on feed intake of Japanese quails. This is similar to the report of Costa et al (2004) that feed intake is not necessarily controlled by protein levels in the diet, although (Dumont et al, 2017) reported an increase in feed intake among birds fed low crude protein level.…”
Section: Experimental Design and Statistical Analysissupporting
confidence: 89%
“…As stated by J. H. V. Silva and Costa (2009), WG decreases in the growth period, possibly because protein and water deposition give place to fat deposition in the carcass and also because the organs require a larger amount of energy from the diet. Moreover, the excess protein and amino acids which are deaminated and N excretion in the form of uric acid by the birds incur energy expenditure by the animal (Dumont et al, 2017). Therefore, excess amino acids or protein does not contribute to improving bird performance.…”
Section: Resultsmentioning
confidence: 99%
“…FRIDRICH et al ( 2005) encontraram melhor conversão alimentar utilizando 25,5% de PB no período de 18 a 28 dias, próximo ao proposto no presente estudo, visto que a medida que a idade das aves evolui a exigência por PB vai diminuindo, devido à redução na taxa de crescimento muscular das aves (MARCARI et al 2002). Os resultados do presente estudo estão próximos também de DUMONT et al (2017), que encontraram melhor desempenho utilizando 26% de PB. A viabilidade diminuiu linearmente com o aumento da PB, demonstrando que o aumento dos valores proteicos da dieta pode elevar a mortalidade das aves (Figura 1C).…”
Section: Resultsunclassified